An empirical study on the drivers of financial leverage of Spanish wind farms - Jorge Blázquez; Marzio Galeotti; José María Martín-Moreno (The Oxford Institute for Energy Studies, 2020)
For renewable energy projects, financing is a major bottleneck to accelerate the transition towards a decarbonized energy mix. Multilateral international institutions are developing new financing instruments to address the barriers and risks that hold back private investment in renewable energy technologies, while minimizing the possibility of crowding out the private sector. Within this context, our study explores the drivers of external financing for Spanish wind farms using a dataset of 318 projects commissioned in the period 2006-13. Thanks to the granularity of this dataset, our analysis provides some results that help explain why some projects are more attractive than others from a financial perspective. This study has three main takeaways. First, the costs of a renewable project are the main drivers that determine the access to external financing, whereas the capacity factor, which determines the revenues, has a minor relevance. Second, the behavior of banks changed after the financial crisis of 2008. Before the crisis, expensive projects tended to have higher debt leverage ratio while after the financial crisis, these projects were penalized in terms of access to external financing. Third, the standard metric to assess the competitiveness of renewable projects, the levelized cost of electricity (LCOE), does not help understand the access to external financing and leverage.
Keywords: 330; capital and operational costs; debt leverage ratio; levelized cost of electricity; wind farms